(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the concept of comparative linguistics, which is the object of study, and analyzes the research of scientists in this field. At the same time, the morphological language units realizing the concept of "goal" in English are compared and their field nature is comparatively studied. Morphological language units in the English language, which are in the field of the target concept, are considered through examples from different literature. At the same time, the variants of the Uzbek language suitable for its language units are thoroughly researched and concluded through examples at the language levels.